Lipopolysaccharide-induced inflammation or unilateral ureteral obstruction yielded multiple types of glycosylated Lipocalin 2. Issue 1 (December 2016) - Fujiwara, Yoko; Tsuchiya, Hiroyoshi; Sakai, Nobuya; Shibata, Katsushi; Fujimura, Akio; Koshimizu, Taka-aki
Abstract Background The amount of urinary glycoprotein lipocalin 2 (LCN2) has been known to increase after kidney injury because of failed reabsorption by the proximal tubules or direct secretion from injured tissues. However, the relationship between urinary tract obstruction and the isoform diversity of LCN2 has not been examined. Methods The urinary levels of LCN2 isoforms were examined in male mice after an intraperitoneal injection of lipopolysaccharide (LPS) or in a mouse model of unilateral ureter obstruction (UUO). The LCN2 levels in sera, bladder urine, renal pelvic urine, and tissue samples were also analyzed. Endo- and exoglycosidases were used to investigate the different N-glycan patterns of LCN2. Results Two isoforms of urinary LCN2 with different molecular weights were identified in an immunoblotting analysis, and the levels of both isoforms were increased 6 h after LPS administration. The primary LCN2 isoform was the lower molecular weight 22-kDa isoform, which was detected in the serum, urine, liver and kidney. In contrast, the 24-kDa LCN2 isoform was detected only in urine. In the UUO experiments, the levels of the 24-kDa LCN2 were increased in the bladder urine but not in the urine accumulated in the renal pelvis due to UUO. The 22-kDa LCN2 was identified in the renal pelvic urine from UUO mice. The peptide-N glycosidase F digestion of the two urinary LCN2 isoforms generated a single protein. Moreover, the two urinary LCN2 proteins were sensitive to neuraminidase and resistant to endoglycosidase H (Endo H). The LCN2 in the serum, lung and kidney was resistant to Endo H, as observed in urine, whereas the LCN2 in the liver and the ureter were degraded by this enzyme. Conclusions These results suggest that the difference in the molecular weights of the LCN2 proteins was due to their N-glycan structure. The high molecular weight LCN2 in urine could be detected after the inflammatory response to LPS and UUO. Furthermore, the sensitivity to Endo H identified the presence of two types of carbohydrate moieties, depending on the tissue in which the LCN2 was produced. These findings are useful for widening the clinical applicability of urinary LCN2 analyses.